Lek hos Stinkpadda (Bufo callamita): jämförelse av restaurerade och ickerestaurerade hällkar - Falk, Malin (2014)
The natterjack toad (Bufo calamita) is one of three species of toads living in Sweden. During the last decades declines in population numbers have been detected and are thought to be primarily due to loss of habitat, overgrown breeding ponds and competition from common toad (Bufo bufo) and common frog (Rana temporaria). In 2012 20 ponds in the location of Glommeskallen in Smögen were restored by clearing the ponds from overgrowth. The aim of this study was to investigate if natterjack toads used the restored ponds and if the restoration had made an impact on the natterjack population on the location. Presence of common toad and common frog was recorded, as was the presence of eggs and larvae of any of the three species. Other potential threats to the natterjack toad were recorded to. As control, the nearby location Holländarberget was chosen because it has an established population of natterjack toads and no restoration has been made to the ponds at the location. Adult natterjack toads and larvae were found at both Glommeskallen and Holländarberget. Eggs, however, were only found at Holländarberget, which was the non-restored site. Statistical analysis showed that the population at Holländarberget was larger than that of the restored Glommeskallen and that more ponds are used by natterjack toads on the former location. However, due to lack of data from before the restoration no conclusions can be drawn on whether or not the restoration of the ponds has increased the population at Glommeskallen. Common toad was found at both sites but more so on Glommeskallen. Common frog and eggs of common frog was found on Glommeskallen only. Potential predators were found at both sites. Smooth newt (Lissotriton vulgaris) was found at both sites and some sort of caddisfly larvae was found at Glommeskallen. Further studies on how these species affect the natterjack toad should be made as part of the conservation effort. To be able to evaluate if the restoration of the ponds at Glommeskallen has had an effect, continuous monitoring of the ponds is recommended.